Lanthanide-based thermometers: At the cutting-edge of luminescence thermometry - Brites, Carlos D. S. (2018)
Present technological demands in disparate areas, such as micro and nanofluidics, micro and nanoelectronics, photonics and biomedicine, among others, have reached to a development such that conventional contact thermal probes are not accomplished to perform accurate measurements with submicrometric spatial resolution. The development of novel non-contact thermal probes is, then, mandatory, contributing for an expansionary epoch of luminescence thermometry. Luminescence thermometry based on trivalent lanthanide ions becomes very popular since 2010 due to the unique versatility, stability and narrow emission band profiles of the ions that cover the entire electromagnetic spectrum with relatively high emission quantum yields. Here we give a perspective overview on the field since the beginnings in the 1950’s until the most recent cutting-edge examples. The current movement towards the technique usage as a new tool for thermal imaging, early tumor detection and as a tool for unveil properties of the thermometers themselves or of their local neighborhoods is also summarized